The Development of Knowledge Enrichment Books Concerning Ice and Snow Physical Studies for High-School Students - Slamet Maulana; Desnita Desnita; Raihanati Raihanati (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
This research aims to develop a knowledge-enrichment physics book of ice and snow that is worthy of use as an enrichment material on physics subject. This research is a research and development with an ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The developed book referred from the Central of Curriculum and Book guideline so that the developed book can be recommended as enrichment material for high-school students. The developed book uses communicative language, attractive illustrations, and information concerning ice and snow with updated science knowledge. The result by physics expert on the developed enrichment book is 94.12% with a category "very good," media expert 87.50% with a category "very good," and with the same category is also given by education expert who gave a score 92.04%. The result of the product trial test shows that students accept the developed enrichment books with "very good," which represent an average score of 90.06%. Based on the validation and product trials test, it concluded that the enrichment book titled â€œIce and Snowâ€ are worthy to be used as enrichment materials on physics.